2015
DOI: 10.1007/s12282-015-0658-z
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of spiritual intervention and changes in dopamine receptor gene expression in breast cancer patients

Abstract: Breast cancer is the most common cancer in females in Iran and in most of the developed countries. Studies have shown that having chronic stress in individuals predisposes several types of cancer including breast cancer. Research results showed that spiritual factors correlate with indices of physical consequences such as heart disease, cancer, and death, so do psychiatric conditions and changes in receptor gene expression in depression, anxiety, and social dysfunction. Different studies demonstrated the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
10
2
Order By: Relevance
“…These are not the only risk factors, also the psychospiritual and social factors will affect the fetus as well as his/her mom (Ariana et al, 2018;Akbari et al, 2016). Our study did not prove the effect of this aspect of health, which may be due to the shortage of number of cases.…”
Section: Discussioncontrasting
confidence: 65%
“…These are not the only risk factors, also the psychospiritual and social factors will affect the fetus as well as his/her mom (Ariana et al, 2018;Akbari et al, 2016). Our study did not prove the effect of this aspect of health, which may be due to the shortage of number of cases.…”
Section: Discussioncontrasting
confidence: 65%
“…Obtained results, as thoroughly explained in our previous study ( 15 ), from peripheral blood mononuclear cell samples analyzed by Real time-PCR collected from patients who underwent the conventional treatment together with the spiritual intervention showed significant reduction in dopamine gene receptor expressions in comparison with those of pre-test scores and the control group ( Tables 2 and 3 ).…”
Section: Resultsmentioning
confidence: 59%
“…Therefore, due to the fact that stressful events can weaken the immune system and transform the disease from primary stages of neoplasm growth to higher stages of cancer ( 40 ), spiritual intervention can generate peace by reducing stress. As a result, by affecting the nervous system, it can regulate and balance in immune cell receptors ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurological processes will decrease pain signals to the brain reducing the pain perception (Sitepu, 2009). Moreover, according to genetic medicine, Zikr is one of spiritual interventions described to reduce cell proliferation in breast cancer patients by changing dopamine receptor gene expression (Akbari, Kashani, Ahangari, Pornour, Hejazi, Nooshinfar, Lotfi, & Hosseini, 2016;Hosseini, Kashani, Akbari, Akbari, & Mehr, 2016) related to the study reported that chronic stress demonstrates dopamine concentration increases leading to an inhibitory effect of T-cells which in turn expands cancer (Mancino, Ametller, Gascón, & Almendro, 2011). Thus, these studies showed that Standing Zikr is a spiritual intervention which can improve in many health outcomes.…”
mentioning
confidence: 99%